Land use/cover change impacts in CMIP5 climate simulations: A new methodology and 21st century challenges. Issue 12 (28th June 2013) - Kumar, Sanjiv; Dirmeyer, Paul A.; Merwade, Venkatesh; DelSole, Timothy; Adams, Jennifer M.; Niyogi, Dev
Abstract : [1] Globally, land use/cover (LU) changes have occurred concurrently with climate change. Several studies have shown significant climate impacts of LU change through sensitivity experiments, which require idealized climate simulations with and without LU change forcings. This paper proposes a new methodology to assess LU change impacts that can be applied to common "all‐forcings" experiments and does not require single‐forcing LU change experiment. The proposed methodology is based on comparing climate change impacts between two neighboring regions in which one region has experienced LU change and the other has not. The methodology is applied to climate simulations from phase 5 of the Coupled Model Intercomparison Project (CMIP5). In the 20th century climate simulations, all 15 climate models examined show a net increase in summer surface albedo, 11 out of 15 models show a net decrease in summer evapotranspiration, and 8 out of 15 models show a net increase in summer temperature in North America and Eurasia LU change regions. In the 8.5 Wm −2 representative concentration pathways (RCP8.5) 21st century climate simulations, all 14 CMIP5 climate models show more summer warming in North America and Eurasia historical LU change regions than in the surrounding regions. We found substantial uncertainties in Africa and South America future LU change regions, where most climate models show a net decrease in summer temperature due to LU change. These uncertainties could be due to the differences in regional climate characteristics, changes in land‐atmosphere interaction in the 21st century, and/or methodological biases. Key Points: A new methodology for LU change impacts in Greater warming in 20th century LU change regions In 21st century, land surface becoming increasingly water‐limited